Deposition of highly oriented diamond films by microwave plasma enhanced CVD - Liao, Xiao Ning. (2010)
In this study, the deposition of {100} textured and highly oriented diamond films has been successfully realized. Investigation was conducted to clarify the influences of various parameters on the growth of {100} textured and highly oriented diamond films. Problems and the growth mechanisms of highly oriented diamond growth have been studied and corresponding solutions for the problems are also discussed. Among the parameters, gas composition and microwave power were found to be the two most influential factors for the textured growth of diamond thin films. Substrate temperature also has a significant effect on the textured growth whereas the influence of gas pressure and flow rate was not significant.